Development of Remote Programming Practice Module for Mitsubishi RV-M1 Industrial Robot - Eko Aris Budi Cahyono; Pippie Arbiyanti; Dian Artanto (Jurnal Teknologi, 2022)
This research aims to provide solutions for practical learning in the vocational field of mechatronic engineering during the Covid-19 pandemic. In order for vocational students to become skilled and competent, a considerable number of hours of practice is required. Meanwhile, to prevent the spread of Covid-19, restrictions on face-to-face meetings have been imposed. To make the number of hours of student practice sufficient without having to meet face to face, a remote laboratory is presented, which can be accessed by students easily, anytime and anywhere. The developed remote laboratory uses real equipment, in the form of the Mitsubishi RV-M1 Industrial Robot, which is monitored by 3 cameras, and can be controlled via the internet. The use of a real robot, not a simulation, is intended so that students can feel the experience as if they were practicing the robot directly. This remote laboratory for the practice of programming the Mitsubishi RV-M1 Industrial Robot has been successfully developed and is already being used by mechatronics students at the vocational faculty of Sanata Dharma University. Most of the students gave a good response to this remote laboratory, because students got a new and interesting experience. To demonstrate the effectiveness of this remote laboratory, a comparison is shown of the average time for searching for the position of an object directly and indirectly through the remote laboratory. From the results of the comparison, the average time to search for the position of an object directly ranges from 1-2 minutes, while through a remote laboratory it ranges from 2-3 minutes, which is considered to be within reasonable limits.